Study Characteristics of Porous Asphalt Using Aggregates from Karangasem with 60/70 Penetration Bitumen - I Gusti Agung Ananda Putra (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Porous asphalt is a type of pavement designed to increase the coefficient of friction on the pavement surface. The porous asphalt functions as drainage to drain water in the top layer vertically and horizontally. The method used in this research is an experimental method by making different tests in the laboratory. Stages of works include examining the 60/70 penetration bitumen, aggregate testing, mixing, and preparation of the sample with the variation of asphalt level of 5%, 5.5%, 6%, 6.5%, and 7% with 2x50 Marshall compaction. Volumetric measurement and Marshall testing to get optimum asphalt level. The next test is the cantabro test, permeability test, ITS test, and UCS test at optimum asphalt level. As the results of this study, it was obtained that the value of the optimum asphalt level was 6.15%, the value of Marshall characteristics, namely stability 636.32 kg (specification min. 500 kg), Flow 4.0 mm (specifications 2-6 mm), Marshall Quotient 159.15 kg/mm (specification max. 400 kg/mm), and Marshall VIM 19.828% (specification of 18-25%). At the optimum asphalt level the samples gave Cantabro value of 17.90% (specification max. 20%), vertical and horizontal permeability values of 0.145 and 0.152 cm/sec (specifications 0.1-0.5 cm/sec), ITS value of 158.88 kPa, and UCS value of 916.343 kPa.